Parents' Nonstandard Work Schedules and Child Well-Being: A Critical Review of the Literature - Jianghong Li; Sarah E. Johnson; Wen-Jui Han; Sonia Andrews; Garth Kendall; Lyndall Strazdins; Alfred Dockery (The Journal of Primary Prevention, 2014)
This paper provides a comprehensive review of empirical evidence linking parental nonstandard work schedules to four main child developmental outcomes: internalizing and externalizing problems, cognitive development, and body mass index. We evaluated the studies based on theory and methodological rigor (longitudinal data, representative samples, consideration of selection and information bias, confounders, moderators, and mediators). Of 23 studies published between 1980 and 2012 that met the selection criteria, 21 reported significant associations between nonstandard work schedules and an adverse child developmental outcome. The associations were partially mediated through parental depressive symptoms, low quality parenting, reduced parent-child interaction and closeness, and a less supportive home environment. These associations were more pronounced in disadvantaged families and when parents worked such schedules full time. We discuss the nuance, strengths, and limitations of the existing studies, and propose recommendations for future research.
Keywords: 330; child mental health; child obesity; cognitive development; nonstandard work schedules; parental employment; shift work